Carbon Nanotube-Based Molecularly Imprinted Voltammetric Sensor for Selective Diuretic Analysis of Dialysate and Hemodialysis Wastewater - de Oliveira, Gabriela F. [UNESP] (2020)
A molecularly imprinted polymer (MIP)-based electrochemical sensor was developed for the monitoring of hydrochlorothiazide (HCT) in dialysate and hemodialysis wastewater. The MIP was constructed by the electropolymerization of ortho-phenylenediamine on multi-walled carbon nanotube modified glassy carbon electrode surface. The experimental optimization was carried out by Plackett-Burman design screening and central composite design. Through square wave voltammetry (SWV) analysis, the sensor presented linear response in the range of 5.0×10−6 to 1.0×10−4 mol L−1 (R=0.9995) and detection limit of 3.2×10−6 mol L−1. The film morphology was investigated by SEM, EDX and AFM, and the electrochemical response was confirmed by EIS. The MIP film exhibited excellent selectivity for HCT, rapid response and good practicability. The sensor was successfully applied for direct and selective determination of HCT in dialysate and hemodialysis wastewater samples with recovery rates ranging from 97 % to 102 % based on the standard addition method.